Double sampling data checking technique an online testing solution for multisource noise-induced errors on on-chip interconnects and buses. - Yi Zhao (IEEE Transactions on VLSI systems)
With processors and system-on-chips using nano-meter technologies, several design and test efforts have been recently developed to eliminate and test for many emerging DSM noise effects. In this paper, we show the emergence of multisource noise effects, where multiple DSM noise sources combine to produce functional and timing errors even when each separate noise source itself does not. We show the dynamic nature of multisource noise, and the need for online testing to detect such noise errors. We propose an online approach based on low-cost double-sampling data checking circuit to test for such noise effects in on-chip buses. Based on the proposed circuit, an effective and efficient testing methodology has been developed to facilitate online testing for generic on-chip buses. The applicability of this methodology is demonstrated through embedding the online detection circuit in a bus design. The validated design shows the effectiveness of the proposed testing methodology for multisource noise-induced errors in global interconnects and buses.